2018
DOI: 10.5194/acp-18-4069-2018
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and sources of atmospheric halocarbons in the Eastern Mediterranean

Abstract: Abstract. A wide range of anthropogenic halocarbons is released to the atmosphere, contributing to stratospheric ozone depletion and global warming. Using measurements of atmospheric abundances for the estimation of halocarbon emissions on the global and regional scale has become an important top-down tool for emission validation in the recent past, but many populated and developing areas of the world are only poorly covered by the existing atmospheric halocarbon measurement network. Here we present 6 months o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Formyl fluoride (HFCO) is a key molecule, produced via atmospheric degradation of hydrofluorocarbons (HFCs) and hydrofluoroolefins (HFOs). HFCs have been used as a refrigerant instead of CFCs and HCFCs to protect the ozone layer . Here, HFC-134a is one of the highest concentrations of HFCs in the atmosphere, which mainly reacts with the OH radical; this leads to the formation of the dominant intermediate product HFCO. In recent years, experimental results have shown that the concentration of HCF-134a has been increasing year by year due to anthropogenic emission; , this leads to the increase of the concentration of HFCO in the atmosphere. Therefore, it is particularly necessary and important for clarifying the atmospheric lifetime of HFCO to fully estimate atmospheric environmental effects of HFCs and HFOs.…”
Section: Introductionmentioning
confidence: 99%
“…Formyl fluoride (HFCO) is a key molecule, produced via atmospheric degradation of hydrofluorocarbons (HFCs) and hydrofluoroolefins (HFOs). HFCs have been used as a refrigerant instead of CFCs and HCFCs to protect the ozone layer . Here, HFC-134a is one of the highest concentrations of HFCs in the atmosphere, which mainly reacts with the OH radical; this leads to the formation of the dominant intermediate product HFCO. In recent years, experimental results have shown that the concentration of HCF-134a has been increasing year by year due to anthropogenic emission; , this leads to the increase of the concentration of HFCO in the atmosphere. Therefore, it is particularly necessary and important for clarifying the atmospheric lifetime of HFCO to fully estimate atmospheric environmental effects of HFCs and HFOs.…”
Section: Introductionmentioning
confidence: 99%
“…The HFC-152a emissions from other countries except China changed with an average growth rate of −0.1 ± 0.2 Gg/yr 2 during 2011–2020. Unfortunately, there were no top-down estimates of HFC-152a emissions from other countries or regions except those listed in Figure S6, especially for the non-Annex I parties, where the estimates were only available for certain years (2005, , 2006, 2008, 2010, 2010–2012, 2013, 2016, and 2017). For example, our top-down estimates trace the HFC-152a emissions in China until 2020, whereas the top-down estimates in the United States have not been estimated since 2012 and the latest top-down estimates from the other countries have become unavailable after 2017 (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…The Empa (Swiss Federal Laboratories for Materials Science and Technology) Bayesian inverse modelling framework (Henne et al (2016)) has been used e.g., to estimate methane emissions in Switzerland and halocarbon emissions in Europe (e.g., Brunner et al, 2017;Schoenenberger et al, 2018;Simmonds et al, 2020) and eastern Asia (Rigby et al, 2019;Park et al, 2021).…”
Section: Empamentioning
confidence: 99%